Activation of YAP/TAZ by gut microbiota via Wnt/β-catenin signaling in cancer development - Shahin Javanmard; Kayhan Ertürk (Academia Molecular Biology and Genomics, 2025)
This review examines the role of gut microbiota in the activation of the Wnt/β-catenin signaling pathway and its impact on cancer progression via YAP/TAZ activation. Yes-associated protein, YAP, is a transcriptional coactivator involved in regulating gene expression and cell proliferation by interacting with TEA domain (TEAD) transcription factor in the Hippo signaling pathway. The Wnt/β-catenin pathway is an evolutionarily conserved pathway that is important for development and tissue homeostasis but was described as driving oncogenic processes through YAP/TAZ activity. In this regard, gut microbiota metabolites drove tumor development by activating the Wnt/β-catenin pathway onto YAP/TAZ activation with increased evidence. This review discusses recent studies on the modulation of gut microbiota and its effect on Wnt/β-catenin signaling and further pursues the effects of cancer treatment and prevention.